TERJADINYA KITAB MAZMUR - Berthold Anton Pareira (Studia Philosophica et Theologica, 2011)
In the last two or three decades, research into the structure and formation of the book of Psalms has offered new understanding of the book, i.e. its unifying editorial purpose. The study is an effort to give a unifying picture of the results of the various studies